O38 Determination of antibodies against SARS-CoV-2 in non-invasively collected human colorectal mucus. (19th June 2022) - Nooredinvand, Hesam Ahmadi; Poullis, Andrew; Ma, Julian; Groppelli, Elisabetta; Loktionov, Alexandre
Abstract : Introduction: The present study aimed to investigate if antibodies against SARS-CoV-2 can be detected in the colorectal mucus (CM) overlaying the internal surface of the gut in COVID-19 patients. This approach could potentially be used for the assessment of the immunological status of individuals recovering from COVID-19 infection. Methods: The presence of anti-COVID antibodies (IgA and IgG) was assessed in samples of colorectal mucus (CM) non-invasively collected (self-collected) from patients hospitalized with COVID-19 infection. Samples were collected from 12 patients with COVID-19 confirmed by positive PCR test for the virus (some of these patients collected samples repeatedly every week) and 8 healthy controls (8 samples) were analysed. The samples were tested for antibodies (either IgA or IgG) against trimeric spike protein of SARS-CoV-2 using in-house ELISA assays. Results: Preliminary results of the analyses are presented in figure 1 . Results for serial sample dilutions are shown for each tested sample. CM samples from cases 4 and 9 collected one week following COVID-19 infection confirmation are positive for antibody presence. Moreover, sample from case 9 collected two weeks following COVID-19 infection confirmation is weakly positive for antibody presence as well. Preliminary results presented in Figure 1 clearly indicate that IgG antibodies against trimeric spike protein of SARS-CoV-2 can be detected in CM samples collected from patients recovering from COVID-19 infection. It is important to note that patients 4 and 9 found to be positive for IgG antibody one week following COVID-19 confirmation were already asymptomatic. These encouraging early results suggest that the peak of anti-SARS-CoV-2 antibodies occurs at least one week following disease development, but further analysis is needed to confirm the existence of this interesting trend. Further work is ongoing to assess IgA antibody detection in CM. Conclusions: The preliminary results of this study indicate that the detection of anti-SARS-CoV-2 IgG antibodies in non-invasively collected CM samples may be used for developing new diagnostic techniques for assessing immunity against COVID-19 infection, especially in asymptomatic individuals. This could also provide a tool for assessing immune status of individuals undergoing anti-COVID vaccination.